Water-blocking oxygen quantum dot combined adhesive as well as preparation method and application thereof

By selecting specific polyurethane, hydrochin resin, fluorosilic acrylic resin lotion and modified SIO2 particles, prepare water -resistant oxygen quantum dot combination glue, solve the problem of poor stability of quantum dot glue under water oxygen, realize high stability and excellent excellent and excellent Optical quantum dot optical membrane.

CN119351006APending Publication Date: 2025-01-24TOMI CHENGDU APPLIED TECH RES INST CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310875550.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing quantum dispenser has extremely poor stability under water oxygen, resulting in reduced or failure of the quantum dot film performance, and insufficient water oxygen barrier properties and uniform light properties, which are costly.

Method used

By selecting a specific polyurethane, hydro -silicon acrylic resin emulsion, and modified SIO2 particles, the synergy is used to prepare water -resistant oxygen quantum dot combination glue to improve its optical properties and compatibility.

Benefits of technology

Significantly improves the stability and optical performance of quantum dot optical films, enhances water and oxygen barrier properties, extends the life of quantum dots, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004351020230000021
    Figure BDA0004351020230000021
  • Figure BDA0004351020230000081
    Figure BDA0004351020230000081
  • Figure BDA0004351020230000091
    Figure BDA0004351020230000091
Patent Text Reader

Abstract

The invention provides a water-blocking oxygen quantum dot combined adhesive as well as a preparation method and application thereof, and the water-blocking oxygen quantum dot combined adhesive is prepared from the following raw materials in parts by weight: 20-50 parts of polyurethane acrylic resin; 25 to 70 parts of adhesive resin; 5-20 parts of a reactive diluent; 1-3 parts of a photoinitiator; 0.01 to 2 parts of red quantum dots; 0.1 to 5 parts of green quantum dots; 0.5 to 20 parts of modified SiO2 particles; 0.01 to 0.05 part of spacer particles; a soft segment structure of the polyurethane acrylic resin contains methyl, and a hard segment structure of the polyurethane acrylic resin contains an annular structure; the reactive diluent comprises a fluorosilicone acrylic resin emulsion. According to the quantum dot combined adhesive disclosed by the invention, the specific polyurethane acrylic resin, the reactive diluent and the modified SiO2 particles are selected and have a synergistic effect, so that the prepared quantum dot combined adhesive has excellent water and oxygen barrier property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quantum dots, and relates to a water-blocking oxygen quantum dot composite adhesive and a preparation method and application thereof. Background Art

[0002] Quantum dots are a new type of semiconductor nanomaterial. Due to their adjustable band gap and excellent luminescence properties, they have attracted much attention and are widely used in many biological and scientific fields such as display imaging and tracing labeling.

[0003] At present, there is still a large gap between cadmium-free quantum dots such as InP and cadmium-based quantum dots CdSe in terms of quantum yield, half-width, stability, and application cost, so cadmium-based quantum dots are the primary research direction; for quantum dot optical films, the stability of quantum dots in water and oxygen is extremely poor. Optical glue, as a carrier of quantum dots, has a barrier property against water and oxygen that directly determines the stability and functionality of quantum dots.

[0004] CN109135628A discloses a quantum dot glue composition and a quantum dot film. The quantum dot glue composition includes: 100 parts by weight of adhesive resin, 0.1-25 parts by weight of inorganic flaky filler, 0.2-20 parts by weight of quantum dots and 1-30 parts by weight of scattering particles. The quantum dot glue composition provided by the invention contains inorganic flaky fillers, and the quantum dot film prepared therefrom exhibits more outstanding performance stability, which can solve the problem that quantum dots are easily corroded by oxygen and water vapor, resulting in reduced performance or failure of the quantum dot film. However, the water-oxygen barrier performance of the quantum dot glue of the invention needs to be further improved, and the uniform light performance is poor, and the cost is relatively high.

[0005] Therefore, it is desirable to develop a water-blocking oxygen quantum dot adhesive in the art. Summary of the invention

[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a water-blocking oxygen quantum dot combination adhesive and a preparation method and application thereof. The water-blocking oxygen quantum dot combination adhesive provided by the present invention is used for a quantum dot optical film to improve the stability and optical properties of the quantum dot optical film.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a water-blocking oxygen quantum dot composite adhesive, wherein the raw materials for preparing the water-blocking oxygen quantum dot composite adhesive include the following components in parts by weight:

[0009]

[0010] The polyurethane acrylic resin contains methyl groups in its soft segment structure and cyclic structures in its hard segment structure;

[0011] The reactive diluent includes fluorosilicone acrylic resin emulsion.

[0012] In the present invention, by selecting a specific polyurethane acrylic resin, a reactive diluent and modified SiO2 particles, the three work synergistically to prepare a quantum dot composite adhesive having excellent water and oxygen barrier properties. Specifically, the molecular chain of the polyurethane acrylic resin is composed of a hard segment and a soft segment. The soft segment is usually a polyether structure. By introducing a hydrophobic methyl group into the soft segment structure, the hydrophilicity can be effectively reduced. Compared with a linear hard segment structure, the photocurable coating of the polyurethane acrylic resin containing a cyclic hard segment structure has a lower water absorption rate. The reactive diluent is a fluorosilicone acrylic resin emulsion. The addition of fluorosilicone is beneficial to improving the hydrophobicity and chemical resistance.

[0013] The present invention optimizes the properties and structure of the components without adding additional components to the quantum dot combination glue, thereby improving its optical performance, and improving the compatibility, dispersibility, water and oxygen barrier properties, light transmittance and uniform light properties of the quantum dot combination glue; and can be adapted to different systems according to needs.

[0014] The polyurethane acrylic resin provided by the present invention can be purchased through commercial channels, for example, LUXYDIR ZHU-1968, LUXYDIR ZHU-2082, LUXYDIR ZHU-1999, DH-JZ004, etc. can be selected; it has excellent glass adhesion and is more suitable for application on glass optical films.

[0015] In the present invention, the raw materials for preparing the water-blocking oxygen quantum dot combination glue are calculated by weight, and the amount of polyurethane acrylic resin used can be 20 parts, 23 parts, 25 parts, 28 parts, 30 parts, 33 parts, 35 parts, 38 parts, 40 parts, 43 parts, 45 parts, 48 ​​parts or 50 parts, etc.

[0016] In the present invention, the raw materials for preparing the water-blocking oxygen quantum dot combination glue are calculated by weight, and the amount of adhesive resin used can be 25 parts, 30 parts, 33 parts, 35 parts, 38 parts, 40 parts, 43 parts, 45 parts, 48 ​​parts, 50 parts, 53 parts, 55 parts, 58 parts, 60 parts, 63 parts, 65 parts, 68 parts or 70 parts, etc.

[0017] In the present invention, the raw materials for preparing the water-blocking oxygen quantum dot combination glue are calculated by weight, and the amount of active diluent used can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts, etc.

[0018] In the present invention, the raw materials for preparing the water-blocking oxygen quantum dot composite adhesive are calculated by weight, and the amount of the photoinitiator used can be 1 part, 2 parts or 3 parts.

[0019] In the present invention, the raw materials for preparing the water-blocking oxygen quantum dot combination glue are calculated by weight, and the amount of red quantum dots used can be 0.01 parts, 0.03 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 parts, 1.3 parts, 1.5 parts, 1.8 parts or 2 parts, etc.

[0020] In the present invention, the raw materials for preparing the water-blocking oxygen quantum dot combination glue are calculated by weight, and the amount of green quantum dots used can be 0.1 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 parts, 2 parts, 3 parts, 4 parts or 5 parts.

[0021] In the present invention, the raw materials for preparing the water-blocking oxygen quantum dot combination glue are calculated by weight, and the amount of modified SiO2 particles used can be 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts, etc.

[0022] In the present invention, the raw materials for preparing the water-blocking oxygen quantum dot combination glue are calculated by weight, and the amount of spacer particles used can be 0.01 parts, 0.02 parts, 0.03 parts, 0.04 parts or 0.05 parts, etc.

[0023] Preferably, the sum of the weight parts of the polyurethane acrylic resin, the adhesive resin, the reactive diluent and the photoinitiator is 100 parts.

[0024] Preferably, the fluorosilicone acrylic resin emulsion is prepared by the following method:

[0025] The base is copolymerized with the organic silicon monomer and the organic fluorine monomer by an emulsion polymerization process to obtain the fluorosilicone acrylic resin emulsion;

[0026] The matrix includes any one of isobornyl acrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate or trimethylolpropane triacrylate or a combination of at least two thereof.

[0027] Preferably, the organic silicon monomer includes any one of monomethylchlorosilane, dimethylchlorosilane, trimethylchlorosilane or hydrogen-containing silane, or a combination of at least two thereof.

[0028] Preferably, the organic fluorine monomer includes any one of tetrafluoroethylene, difluoro-chloromethane, trifluorochloroethylene or hexafluoropropylene, or a combination of at least two thereof.

[0029] Preferably, the mass ratio of the substrate to the organic silicon monomer and the organic fluorine monomer is 100:(0.5-1.5):(3-9), for example, 100:1:3, 100:0.5:3, 100:1.5:3, 100:1:6, 100:1:9, 100:1.5:3, 100:1.5:6 or 100:1.5:9, etc.

[0030] Preferably, the copolymerization temperature is 70-90°C, such as 70°C, 80°C or 90°C, etc., and the time is 0.5-3h, such as 0.5h, 1h, 2h or 3h, etc.

[0031] Preferably, the modified SiO2 particles are prepared by the following method:

[0032] The SiO2 particles are modified by using a hydrophobic modifier using a sol-gel method to obtain the modified SiO2 particles;

[0033] The hydrophobic modifier includes any one of hexamethyldisilazane, trimethylchlorosilane, methyltrimethoxysilane or phenyltrimethoxysilane, or a combination of at least two thereof.

[0034] In the present invention, the modified SiO2 particles have a micro-nano rough structure with a lotus leaf effect and have super hydrophobic properties. In addition, the modified SiO2 particles also have diffusion efficiency and can improve the uniform light effect.

[0035] Preferably, the mass ratio of the hydrophobic modifier to the SiO2 particles is 2:(1-6), for example, 2:1, 2:2, 2:3, 2:4, 2:5 or 2:6.

[0036] Preferably, the particle size of the modified SiO2 particles is 300-400 nm, for example, 300 nm, 310 nm, 320 nm, 330 nm, 340 nm, 350 nm, 360 nm, 370 nm, 380 nm, 390 nm or 400 nm, etc. When the particle size of the modified SiO2 particles is within the above range, they have more excellent hydrophobic properties.

[0037] Preferably, the adhesive resin includes any one of urea-formaldehyde resin, polyvinyl acetate, polyacrylic acid resin, polyacrylic acid resin or polyurethane, or a combination of at least two of them.

[0038] Preferably, the photoinitiator comprises TPO and / or 184.

[0039] Preferably, the raw materials for preparing the water-blocking oxygen quantum dot combination glue also include auxiliary agents.

[0040] Preferably, the weight proportion of the auxiliary agent is 0.1-5 parts, for example, 0.1 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 parts, 2 parts, 3 parts, 4 parts or 5 parts.

[0041] Preferably, the auxiliary agent includes a defoamer and / or a leveling agent.

[0042] Preferably, the red quantum dots are of CdSe / ZnSeS / ZnS structure.

[0043] Preferably, the green quantum dots are of CdSe / ZnSeS / ZnS structure.

[0044] Preferably, the spacer particles include any one of polymethyl methacrylate (PMMA), modified polybutyl methacrylate (PBMA), modified polystyrene (PS), polystyrene or silicon dioxide (SiO2) or a combination of at least two thereof. When the quantum dot optical film is subsequently prepared, the presence of the spacer particles facilitates the control of the film thickness.

[0045] In a second aspect, the present invention provides a method for preparing the water-blocking oxygen quantum dot composite glue as described in the first aspect, the preparation method comprising the following steps:

[0046] (1) mixing the active diluent with the red quantum dots and the green quantum dots, and stirring until clear to obtain a first mixture;

[0047] (2) mixing a polyurethane acrylic resin, an adhesive resin and a photoinitiator to obtain a second mixture;

[0048] (3) Add the first mixture to the second mixture, stir until it is transparent and free of particles, then add modified SiO2 particles, spacer particles and optional auxiliary agents, mix to obtain the water-blocking oxygen quantum dot composite glue, and store it by standing or vacuum method.

[0049] Preferably, step (2) specifically includes the following steps: placing the polyurethane acrylic resin, adhesive resin and photoinitiator in an oven and heating them to 80-85°C (for example, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C) to facilitate uniform dissolution of the three components, and then placing them on a heated stirring table and stirring them at a constant temperature of 25°C at a rate of 80-120rpm (for example, 80rpm, 90rpm, 100rpm, 110rpm or 120rpm, etc.) to obtain a second mixture.

[0050] In a third aspect, the present invention provides a quantum dot optical film, comprising a first transparent base layer, a quantum dot glue layer, and a second transparent base layer stacked in sequence, wherein the quantum dot glue layer is obtained by curing the water-blocking oxygen quantum dot combination glue described in the first aspect.

[0051] Preferably, the thickness of the quantum dot glue layer is 70-120 μm, for example, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm or 120 μm.

[0052] Preferably, the thickness of the first transparent base layer is 70-100 μm, for example, 70 μm, 80 μm, 90 μm or 100 μm.

[0053] Preferably, the second transparent base layer has a thickness of 70-100 μm, such as 70 μm, 80 μm, 90 μm or 100 μm.

[0054] Preferably, the materials of the first transparent base layer and the second transparent base layer are independently selected from any one or a combination of at least two of polyethylene terephthalate (PET), polyamide resin (PA), polycarbonate (PC), polystyrene (PS), polyethylene (PE), polypropylene (PP), polymethyl methacrylate (PMMA) or SiO2.

[0055] The present invention does not specifically limit the method for preparing the quantum dot optical film. Exemplarily, the method for preparing the quantum dot optical film comprises the following steps:

[0056] A first transparent base layer is selected, and vacuum adsorption positioning is performed using a coating device. The water-blocking oxygen quantum dot combination glue described in the first aspect is applied to the first transparent base layer by slit coating or scraping, and the second transparent base layer is aligned and covered, UV-cured, and then the frame-sealing glue is applied to the edge and cured to obtain the quantum dot optical film.

[0057] In a fourth aspect, the present invention provides an application of the quantum dot optical film as described in the first aspect in quantum dot luminescent materials, vehicle-mounted displays, lighting or tracking markers.

[0058] Compared with the prior art, the present invention has at least the following beneficial effects:

[0059] In the present invention, by selecting a specific polyurethane acrylic resin, a reactive diluent and modified SiO2 particles, the three work synergistically to prepare a quantum dot composite adhesive having excellent water and oxygen barrier properties (when the test time reaches 600h, the attenuation at the edge is still less than 20%). Specifically, the molecular chain of the polyurethane acrylic resin is composed of a hard segment and a soft segment. The soft segment is usually a polyether structure. The hydrophilicity can be effectively reduced by introducing a hydrophobic methyl group into the soft segment structure. Compared with a straight-chain hard segment structure, the light-cured coating of the polyurethane acrylic resin containing a cyclic hard segment structure has a lower water absorption rate. The reactive diluent is a fluorosilicone acrylic resin emulsion. The addition of fluorosilicone is beneficial to improving the hydrophobicity and chemical resistance. DETAILED DESCRIPTION

[0060] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0061] Preparation Example 1

[0062] In this preparation example, a fluorosilicone acrylic resin emulsion is provided, and the preparation method is as follows:

[0063] The base is copolymerized with the organic silicon monomer and the organic fluorine monomer at 85° C. for 2 hours by an emulsion polymerization process to obtain the fluorosilicone acrylic resin emulsion;

[0064] The matrix is ​​isobornyl acrylate, the organosilicon monomer is monomethylchlorosilane, and the organofluorine monomer is tetrafluoroethylene; the mass ratio of the matrix to the organosilicon monomer and the organofluorine monomer is 100:1:6.

[0065] Preparation Example 2

[0066] In this preparation example, a modified SiO2 particle is provided, and the preparation method is as follows:

[0067] The SiO2 particles are modified by using a hydrophobic modifier using a sol-gel method to obtain the modified SiO2 particles.

[0068] Among them, the hydrophobic modifier is hexamethyldisilazane; the mass ratio of the hydrophobic modifier to the SiO2 particles is 2:1; and the particle size of the modified SiO2 particles is 320nm.

[0069] Examples 1-6

[0070] In Examples 1-6, a water-blocking oxygen quantum dot composite glue is provided respectively. The raw materials and dosage (weight parts) of the water-blocking oxygen quantum dot composite glue are shown in Table 1. The preparation method comprises the following steps:

[0071] (1) mixing the active diluent with the red quantum dots and the green quantum dots, and stirring until clear to obtain a first mixture;

[0072] (2) mixing the polyurethane acrylic resin, the adhesive resin and the photoinitiator, placing the mixture in an oven and heating it to 85° C. to uniformly dissolve the three components, and then placing the mixture on a heated stirring table and stirring the mixture at a constant temperature of 25° C. at a rate of 100 rpm to obtain a second mixture;

[0073] (3) Add the first mixture to the second mixture, stir until it is transparent and free of particles, then add modified SiO2 particles and spacer particles, mix, and obtain the water-blocking oxygen quantum dot composite glue.

[0074] Table 1

[0075]

[0076]

[0077] Comparative Example 1

[0078] The only difference between this comparative example and Example 1 is that the polyurethane acrylic resin is replaced by an equal weight portion of melamine resin.

[0079] Comparative Example 2

[0080] The only difference between this comparative example and Example 1 is that the reactive diluent fluorosilicone acrylic resin emulsion is replaced by an equal weight portion of 1,6-hexanediol diacrylate.

[0081] Comparative Example 3

[0082] The only difference between this comparative example and Example 1 is that the modified SiO2 particles are replaced by unmodified SiO2 particles in equal parts by weight.

[0083] Comparative Example 4

[0084] The only difference between this comparative example and Example 1 is that the weight portion of the polyurethane acrylic resin is 15 parts, and correspondingly, the weight portion of the adhesive resin is adjusted to 73 parts.

[0085] Comparative Example 5

[0086] The only difference between this comparative example and Example 1 is that the weight portion of the active diluent is 2 parts, and correspondingly, the weight portion of the adhesive resin is adjusted to 71 parts.

[0087] Comparative Example 6

[0088] The only difference between this comparative example and Example 1 is that the weight portion of the modified SiO2 particles is 1 part.

[0089] Application Examples 1-6 and Comparative Application Examples 1-6

[0090] A quantum dot optical film is provided in Application Examples 1-6 and Comparative Application Examples 1-6 respectively. The quantum dot optical film comprises a first transparent base layer, a quantum dot glue layer, and a second transparent base layer stacked in sequence. The quantum dot glue layer is obtained by curing the water-blocking oxygen quantum dot combination glue provided in Examples 1-6 and Comparative Examples 1-6 respectively.

[0091] The thickness of the quantum dot glue layer is 80 μm; the material of the first transparent base layer is polyethylene (PE), and the thickness is 80 μm; the material of the second transparent base layer is polyethylene (PE), and the thickness is 80 μm.

[0092] The preparation method comprises the following steps:

[0093] The first transparent base layer is vacuum adsorbed and positioned by a coating device, and the water-blocking oxygen quantum dot combination glue provided by Examples 1-6 and Comparative Examples 1-6 is respectively scraped onto the first transparent base layer, the second transparent base layer is aligned and covered, UV-cured, and then the frame-sealing glue is coated on the edge and cured to obtain the quantum dot optical film.

[0094] The quantum dot optical film provided by the corresponding use case 1-6 and the comparative application example 1-6 was subjected to a double 85 reliability test. The test method is as follows: the prepared quantum dot optical film is placed in a high temperature and humidity alternating chamber for RA test (reliability test). The RA conditions are: temperature is 85°C and humidity is 85% RH. Then the brightness is tested every 100 hours using a CS-2000 spectroradiometer, with a 20% attenuation at the edge as the interruption test index. The smaller the brightness attenuation and the longer the continuous test time, the higher the water and oxygen barrier performance of the quantum dot optical film and the longer the service life.

[0095] The performance test results are shown in Table 2.

[0096] Table 2

[0097]

[0098]

[0099] It can be seen from Table 2 that the quantum dot optical films provided in the application examples of the present invention all have good water and oxygen barrier properties. When the test time reaches 600 hours, the attenuation at the edge is still less than 20%.

[0100] Compared with Application Example 1, the quantum yield attenuation phenomenon of the quantum dot optical films provided in Comparative Application Examples 1-6 is more obvious, and the water and oxygen barrier properties are significantly deteriorated.

[0101] In summary, the quantum dot combination glue provided by the present invention increases the life of quantum dots, delays the attenuation of quantum yield, and has good water and oxygen barrier properties.

[0102] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the water-blocking oxygen quantum dot combination glue of the present invention and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A water-blocking oxygen quantum dot composite adhesive, characterized in that: The raw materials for preparing the water-blocking oxygen quantum dot composite glue include the following components in parts by weight: The polyurethane acrylic resin contains methyl groups in its soft segment structure and cyclic structures in its hard segment structure; The reactive diluent includes fluorosilicone acrylic resin emulsion.

2. The water-blocking oxygen quantum dot composite adhesive according to claim 1, characterized in that: The total weight of the polyurethane acrylic resin, adhesive resin, active diluent and photoinitiator is 100 parts.

3. The water-blocking oxygen quantum dot composite adhesive according to claim 1 or 2, characterized in that: The fluorosilicone acrylic resin emulsion is prepared by the following method: The base is copolymerized with the organic silicon monomer and the organic fluorine monomer by an emulsion polymerization process to obtain the fluorosilicone acrylic resin emulsion; The matrix comprises any one or a combination of at least two of isobornyl acrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate or trimethylolpropane triacrylate; Preferably, the organosilicon monomer includes any one of monomethylchlorosilane, dimethylchlorosilane, trimethylchlorosilane or hydrogen-containing silane, or a combination of at least two thereof; Preferably, the organic fluorine monomer includes any one of tetrafluoroethylene, difluoro-chloromethane, trifluorochloroethylene or hexafluoropropylene, or a combination of at least two thereof; Preferably, the mass ratio of the matrix to the organic silicon monomer and the organic fluorine monomer is 100:(0.5-1.5):(3-9); Preferably, the copolymerization temperature is 70-90° C. and the time is 0.5-3 h.

4. The water-blocking oxygen quantum dot composite adhesive according to any one of claims 1 to 3, characterized in that: The modified SiO2 particles are prepared by the following method: The SiO2 particles are modified by using a hydrophobic modifier using a sol-gel method to obtain the modified SiO2 particles; The hydrophobic modifier includes any one of hexamethyldisilazane, trimethylchlorosilane, methyltrimethoxysilane or phenyltrimethoxysilane, or a combination of at least two thereof; Preferably, the mass ratio of the hydrophobic modifier to the SiO2 particles is 2:(1-6); Preferably, the particle size of the modified SiO2 particles is 300-400 nm.

5. The water-blocking oxygen quantum dot composite adhesive according to any one of claims 1 to 4, characterized in that: The adhesive resin includes any one of urea-formaldehyde resin, polyvinyl acetate, polyacrylic acid resin, polyacrylic acid resin or polyurethane, or a combination of at least two thereof; Preferably, the raw materials for preparing the water-blocking oxygen quantum dot composite glue also include auxiliary agents; Preferably, the weight portion of the auxiliary agent is 0.1-5 parts; Preferably, the red quantum dots are of CdSe / ZnSeS / ZnS structure; Preferably, the green quantum dots are of CdSe / ZnSeS / ZnS structure; Preferably, the spacer particles include any one of polymethyl methacrylate, modified polybutyl methacrylate, modified polystyrene, polystyrene or silicon dioxide, or a combination of at least two thereof.

6. The method for preparing the water-blocking oxygen quantum dot composite adhesive according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) mixing the active diluent with the red quantum dots and the green quantum dots, and stirring until clear to obtain a first mixture; (2) mixing a polyurethane acrylic resin, an adhesive resin and a photoinitiator to obtain a second mixture; (3) Add the first mixture to the second mixture, stir until it is transparent and free of particles, then add modified SiO2 particles, spacer particles and optional additives, mix, and obtain the water-blocking oxygen quantum dot composite glue.

7. A quantum dot optical film, characterized in that: The quantum dot optical film comprises a first transparent base layer, a quantum dot glue layer, and a second transparent base layer which are stacked in sequence, and the quantum dot glue layer is obtained by curing the water-blocking oxygen quantum dot combination glue according to any one of claims 1 to 5.

8. The quantum dot optical film according to claim 7, characterized in that: The thickness of the quantum dot glue layer is 70-120 μm; Preferably, the thickness of the first transparent base layer is 70-100 μm; Preferably, the second transparent base layer has a thickness of 70-100 μm.

9. The quantum dot optical film according to claim 7 or 8, characterized in that: The materials of the first transparent base layer and the second transparent base layer are independently selected from any one of polyethylene terephthalate, polyamide resin, polycarbonate, polystyrene, polyethylene, polypropylene, polymethyl methacrylate or SiO2, or a combination of at least two thereof.

10. Use of the quantum dot optical film according to any one of claims 7 to 9 in quantum dot luminescent materials, vehicle-mounted displays, lighting or tracking markers.

Citation Information

Patent Citations

  • Quantum dot glue composite and quantum dot film

    CN109135628A